Dukungan Sosial yang Diterima oleh Perempuan yang Belum Berhasil Dalam Pengobatan Infertilitas - Anggraeni, Mekar Dwi (Jurusan Keperawatan FIKES UNSOED, 2009)
Infertility and its treatment may cause life crises in infertile women. As a matter of fact, the succes of infertility therapy has not reached 100 percent yet, this problem can lead a woman to have an increassed stress when failure occurs. The purpose of this qualitative descriptive study to explore the phenomenon of women’s experience with infertility in the afternath of unsuccessful medical treatment. Six partisipants was gained by purposive sampling method. Data collection was obtained through deep interview complemented with field data. Interview was recorded, transcripted, and then was analyzed using Collaizz’s method. The result of this study have three main topics are: (1) Self perception, (2) People who are meaningfull in my live, (3) Support which make me stronger. This study result give an useful information for maternity nursing to many requirement and expectation in woman’s health that unsuccessful infertility treatment especially social support needs.